Association between dietary pattern and cardiometabolic risk in children and adolescents: a systematic review - Naruna Pereira Rocha; Luana Cupertino Milagres; Giana Zarbato Longo; Andréia Queiroz Ribeiro; Juliana Farias de Novaes (Elsevier, 2017)
Objective: To evaluate the association between dietary patterns and cardiometabolic risk factors in children and adolescents. Data source: This article followed the recommendations of PRISMA, which aims to guide review publications in the health area. The article search strategy included searches in the electronic databases MEDLINE via PubMed, Scopus, and LILACS. There was no date limitation for publications. The descriptors were used in English according to MeSH and in Portuguese according to DeCS. Only articles on dietary patterns extracted by the a posteriori methodology were included. The question to be answered was: how much can an "unhealthy" dietary pattern influence biochemical and inflammatory markers in this population? Data synthesis: The studies showed an association between dietary patterns and cardiometabolic alterations. The patterns were characterized as unhealthy when associated to the consumption of ultraprocessed products, poor in fiber and rich in sodium, fat, and refined carbohydrates. Despite the associations, in several studies, the strength of this association for some risk markers was reduced or lost after adjusting for confounding variables. Conclusion: There was a positive association between "unhealthy" dietary patterns and cardiometabolic alterations in children and adolescents. Some unconfirmed associations may be related to the difficulty of assessing food consumption. Nevertheless, studies involving dietary patterns and their association with risk factors should be performed in children and adolescents, aiming at interventions and early changes in dietary habits considered to be inadequate. Resumo: Objetivo: Avaliar a associação encontrada nos estudos entre padrão alimentar e fatores de risco cardiometabólicos em crianças e adolescentes. Fonte dos dados: Este artigo seguiu as recomendações do PRISMA, que objetiva orientar as publicações de revisão na área da saúde. A estratégia de busca dos artigos incluiu pesquisas nas bases eletrônicas Medline via PubMed, Scopus e Lilacs. Não houve data limite de publicação. Os descritores foram usados em inglês de acordo com MeSH e em português segundo os DeCS. Apenas artigos de padrão alimentar extraídos pela metodologia a posteriori foram incluídos. A pergunta a ser respondida foi: quanto um padrão alimentar "não saudável" pode influenciar nos marcadores bioquímicos e inflamatórios dessa população. Síntese dos dados: Os estudos demonstraram haver associação entre os padrões alimentares e alterações cardiometabólicas. Os padrões caracterizados como não saudáveis eram marcados pelo consumo de produtos ultraprocessados, pobres em fibras e ricos em sódio, gordura e carboidratos refinados. Apesar das associações, em vários estudos, a força dessa associação para alguns marcadores de risco era reduzida ou perdida após os ajustes para as variáveis de confusão. Conclusão: Houve associação positiva entre os padrões alimentares "não saudáveis" e as alterações cardiometabólicas em crianças e adolescentes. Algumas associações não confirmadas podem estar relacionadas a própria dificuldade de avaliar o consumo alimentar. Apesar disso, estudos envolvendo padrões alimentares e sua associação a fatores de risco devem ser realizados em crianças e adolescentes objetivando intervenções e modificações precoces nos hábitos alimentares tidos como não adequados. Keywords: Dietary, Patterns, Cardiovascular, Children, Adolescent, Palavras-chave: Alimentação, Padrões, Cardiovascular, Crianças, Adolescente